Ambiguity and Time-Varying Risk Aversion in Sovereign Debt Markets - Christoph Grosse Steffen; Maximilian Podstawski (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper introduces changes in the level of ambiguity as a complementary source of time-varying risk aversion. We show in a consumption-based asset pricing model with simultaneously risky and ambiguous assets that a rise in the level of ambiguity raises investors' risk aversion. The effect is quantified in an application to European sovereign debt markets using a structural VAR to achieve identification in the data.
Keywords: C32; D80; E43; G01; H63; 330